2018
DOI: 10.3390/fermentation4030056
|View full text |Cite
|
Sign up to set email alerts
|

Lachancea thermotolerans, the Non-Saccharomyces Yeast that Reduces the Volatile Acidity of Wines

Abstract: Abstract:To improve the quality of fermented drinks, or more specifically, wine, some strains of yeast have been isolated, tested and studied, such as Saccharomyces and non-Saccharomyces. Some non-conventional yeasts present good fermentative capacities and are able to ferment in quite undesirable conditions, such as the case of must, or wines that have a high concentration of acetic acid. One of those yeasts is Lachancea thermotolerants (L. thermotolerans), which has been studied for its use in wine due to it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 32 publications
2
54
0
Order By: Relevance
“…Apart from strain Biodiva, yeasts showed a significant acetic acid utilisation but a lack of production. This aligns with the previous studies (Vilela, ; Porter et al , ), which showed that some strains of L. thermotolerans exhibited acetic acid consumption especially in aerated fermentations, while the lack of acetic acid production by T. delbrueckii and L. thermotolerans has also been reported during lychee and grape wine fermentations (Kapsopoulou et al , ; Chen et al , ). The observed decrease in acetic acid is associated with its activation for acetyl‐CoA synthesis which can subsequently be diverted to generate various by‐products such as higher alcohols and acetate esters.…”
Section: Ph Total Soluble Solids and Sugar Changes During Fermentationsupporting
confidence: 92%
“…Apart from strain Biodiva, yeasts showed a significant acetic acid utilisation but a lack of production. This aligns with the previous studies (Vilela, ; Porter et al , ), which showed that some strains of L. thermotolerans exhibited acetic acid consumption especially in aerated fermentations, while the lack of acetic acid production by T. delbrueckii and L. thermotolerans has also been reported during lychee and grape wine fermentations (Kapsopoulou et al , ; Chen et al , ). The observed decrease in acetic acid is associated with its activation for acetyl‐CoA synthesis which can subsequently be diverted to generate various by‐products such as higher alcohols and acetate esters.…”
Section: Ph Total Soluble Solids and Sugar Changes During Fermentationsupporting
confidence: 92%
“…The fermentation with S. cerevisiae and the sequential fermentation with L. thermotolerans have lower pH levels, whereas the sequential fermentations with T. delbrueckii, M. pulcherrima and P. kluyveri have higher levels. Higher pH differences of L. thermotolerans with the other fermentations may be expected because of its high production of lactic acid [28,66,67]. Some studies confirm that even if lactic acid production is significantly higher for mixed fermentation with L. thermotolerans and S. cerevisiae than a single inoculation with the latter, the pH level can be significantly the same [58,59].…”
Section: Chemical Monitoringmentioning
confidence: 96%
“…thermotolerans also has other interesting properties. Some authors have described L. thermotolerans as an interesting resource that can be employed to reduce the final concentration of volatile acidity in wine [85]. Some studies have reported that L. thermotolerans fermentations produce lower concentrations of acetic acid than S. cerevisiae, by about 0.24 g/L [82,84], while other authors have reported smaller differences in sequential fermentations of about 0.05 g/L [36,86].…”
Section: Lachancea Thermotoleransmentioning
confidence: 99%